Uzbekistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper reviews economic developments in the Republic of Uzbekistan during the 1990s. After several years of high inflation, the thrust of financial policies was shifted toward stabilizing prices and the exchange rate in late 1994, following the introduction of the national currency. In 1995, stabilization and structural reform efforts were intensified, and the authorities' economic program for 1995 was supported by a first drawing under the IMF's Systemic Transformation Facility and a rehabilitation loan from the World Bank.